ANALISIS PENGARUH PREDIKTOR FRAUD DETECTION - Satiman Satiman; Suparmin Suparmin (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
This study aims to provide empirical evidence of the influence of professional skepticism, auditor experience and auditor independence on fraud detection. This type of research is quantitative descriptive.The population in this study is the auditor who works in the Public Accountant Office (KAP) in the South Jakarta area affiliated in the directory of the Indonesian Institute of Certified Public Accountants. The sample used in this study is the auditor, which amounted to 151 respondents. Data was collected by distributing questionnaires by convenience sampling method. The collected data was analyzed using multiple linear regression. Based on the results conducted in this study, it was found that professional skepticism and auditor experience had a significant effect on fraud detection but auditor independence did not significantly influence fraud detection. While jointly showing that professional skepticism, auditor experience and auditor independence influence fraud detection